Endoplasmic reticulum protein 29 (ERp29) as a novel prognostic marker and tumor suppressor in osteosarcoma - Parunya Chaiyawat (2019)
© 2019 Background: Diverse aberrancy in genetic background, protein profiling, and biological pathways have emerged as important factors hindering discovery of effective treatment of osteosarcoma. In a previous study, we used a proteomic approach to identify some osteosarcoma-related proteins by analysis of protein profiling in individual patients through primary cell culture. Endoplasmic reticulum protein 29 (ERp29) emerged as a protein of interest for further study since accumulating evidence suggests it has broad functions in tumorigenesis of different types of cancer. Importantly, until now no report on examination of the expression patterns of ERp29 in osteosarcoma has been published. Methods: In this study, an expression of ERp29 was examined in patient-derived osteosarcoma cells (7 cases) and normal bone graft-derived osteoblasts (7 cases) using western blotting. Expression profile of ERp29 in 94 osteosarcoma cases was investigated using immunohistochemically stained on formalin-fixed paraffin-embedded biopsied tissue. An association with clinicopathologic parameters and the patient survival was evaluated. The doubling time of five osteosarcoma cells lines expressing different levels of ERp29 was determined by a cell number along the exponential phase of the growth curve. Results: The results substantiate the outcome from the proteomic study in which ERp29 expression was significantly higher in primary osteosarcoma cells compared to osteoblastic cells. Immunohistochemical analysis found that expression of ERp29 was low in 79% of the cases (immunoreactive score (IRS) <6). A significant correlation was observed between expression of ERp29 and patient survival. Lower expression of ERp29 (IRS<6) was statistically significantly associated with shorter overall survival of the patients (P = 0.041). In addition, we found that osteosarcoma cells with low ERp29 expression had a higher growth rate compared with high-ERp29-expressing cells. Conclusions: These findings suggest a tumor suppressive role of ERp29 in osteosarcoma. In addition, ERp29 might potentially be applied as a prognostic indicator in patients with osteosarcoma.